2000
DOI: 10.1074/jbc.275.2.921
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein α Subunit Has a Key Role in Determining the Specificity of Coupling to, but Not the Activation of, G Protein-gated Inwardly Rectifying K+ Channels

Abstract: In neuronal and atrial tissue, G protein-gated inwardly rectifying K ؉ channels (Kir3.x family) are responsible for mediating inhibitory postsynaptic potentials and slowing the heart rate. They are activated by G␤␥ dimers released in response to the stimulation of receptors coupled to inhibitory G proteins of the G i/o family but not receptors coupled to the stimulatory G protein G s . We have used biochemical, electrophysiological, and molecular biology techniques to examine this specificity of channel activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 60 publications
5
94
0
Order By: Relevance
“…No such differences are known for the classical PTX-sensitive inhibitory G a subunits, G i a1-3 (Taussig and Gilman 1995;Sunahara et al 1996). These regulatory patterns indicate that the functional significance of heterogeneity at the level of inhibitory G proteins lies not exclusively in conferring specificity to receptor/G coupling (Kleuss et al 1991;Leaney et al 2000). Instead, they open the opportunity for the existence of multiple inhibitory AC pathways within a single cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No such differences are known for the classical PTX-sensitive inhibitory G a subunits, G i a1-3 (Taussig and Gilman 1995;Sunahara et al 1996). These regulatory patterns indicate that the functional significance of heterogeneity at the level of inhibitory G proteins lies not exclusively in conferring specificity to receptor/G coupling (Kleuss et al 1991;Leaney et al 2000). Instead, they open the opportunity for the existence of multiple inhibitory AC pathways within a single cell.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the signal transduction pathway mediating tolerance/dependence is hampered by the ability of ORs to activate multiple inhibitory G proteins and intracellular effector systems (Gudermann et al 1992). Several experimental approaches have been employed to elucidate the specificity of signal transduction cascades in situ, such as application of site-directed anti-G protein antibodies (Simonds et al 1989), antisense strategies (Kleuss et al 1991), and over-expression of genetically modified PTXresistant inhibitory G a subunits (Leaney et al 2000). However, each of these approaches failed to define specific inhibitory AC signalling pathways most likely because of a pronounced functional redundancy between inhibitory G a subunits (Tang et al 1991;Sunahara et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Using the whole-cell configuration of the patch-clamp technique we studied receptor-mediated G protein-gated Kir channel currents in a HEK293 stable cell line robustly expressing the Kir3.1ϩ3.2A channel complex (31). To apply agonists we used a rapid and localized drug-perfusion system that enabled us to apply and remove agonist in under 0.25 s. We used five different dual-receptor and channel stable lines to investigate receptormediated Kir3.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-culture methods and the generation of stable cell lines were as described (30,31). In addition to the stable lines wae have described previously [Kir3.1ϩ3.2A channel plus either the A 1 adenosine receptor (HKIR3.1͞3.2͞A1) or the D 2S dopaminergic receptor (HKIR3.1͞3.2͞D2)], we used a further three-dualreceptor ϩ channel stable lines that were denoted as ␣ 2A adrenergic receptor (HKIR3.1͞3.2͞␣2), GABA-B 1b/2 receptor (HKIR3.1͞3.2͞ GGB), and M 4 -muscarinic receptor (HKIR3.1͞3.2͞M4).…”
Section: Methodsmentioning
confidence: 99%
“…Anionic phospholipids particularly phosphatidylinositol- [4,5]-bisphosphate and sodium are known to be key modulators of the gating and a number of site-directed mutagenesis studies together with structural work have suggested models predicting how this might occur [3840]. However the inhibitory G-protein α subunit also participates in determining the selectivity of activation but not directly in activation itself [41]. There are strands of evidence pointing to models in which the inhibitory heterotrimeric G-protein is complexed with the channel and receptor prior to activation [4246].…”
Section: G-protein Gated Inwardly Rectifying Potassium (Girk) Currentmentioning
confidence: 99%